Synergism of Extruded and Monolithic Co-Mo/?-Al2o3-Sepiolite Catalytic Systems in the Hydrodesulphurization Reaction - Gil-Llambias, F; Villarroel-Jorquera, M; Villarroel-Jorquera, M (Kluwer Academic Publishers, 2016)
This study evaluates the synergism of γ-alumina supported cobalt-molybdenum samples prepared by impregnation in excess of solvent. These materials were then agglomerated with sepiolite in order to obtain samples of extruded cylinders and honeycomb monoliths shaped. The activity of the gas-oil hydrodesulphurization reaction was measured under reaction conditions similar to those used in industry, and the samples were characterised by using electron probe micro analysis and scanning electron microscopy. It was observed that catalytic activity and synergism are higher in both, the extruded and the monolithic samples, when both, the cobalt and molybdenum were impregnated on separate surfaces (Co//Mo), where it was also possible to observe synergism due to hydrogen spillover. The lowest level of activity observed in the extruded and monolithic bimetallic catalysts (CoMo) may be attributed to the cobalt covering the molybdenum active sites. © 2015 Springer Science+Business Media New York.